Pengaruh Media Sosial terhadap Kesadaran Politik Mahasiswa di Era Post-Truth: Analisis Data Kuesioner Mahasiswa Universitas Palangka Raya - Fahrul Fahlevi; Aprianur Aprianur; Aufa Ahmad; Markcelino Mahendra; Arjunna Arjunna; Nabilla Syahvalensi; Bhayu Rhama (UNIVED PRESS, Universitas Dehasen Bengkulu, 2026)
This study aims to analyze the influence of social media on students' political awareness in the post-truth era by emphasizing the relationship between social media intensity, digital literacy, political perception, and political awareness and participation. This research employed a descriptive quantitative approach using a five-point Likert-scale questionnaire administered to 36 university students. The questionnaire items were grouped into four dimensions: intensity of social media use and exposure, digital literacy and information verification, the influence of social media on political perception, and students' political awareness and participation. The findings show that the dimension of social media use and exposure obtained the highest mean score of 4.14. The dimension of social media influence on political perception reached 4.01, while digital literacy and information verification obtained a mean score of 4.01. Students' political awareness and participation recorded the lowest mean score of 3.65. These findings indicate that students are highly exposed to political information on social media and have fairly good critical awareness, yet active political participation such as joining online political discussions, signing online petitions, and sharing political content remains relatively lower.